Pectoralis Muscle Mass on Chest CT at Admission Predicts Prognosis in Patients with Pneumonia - Ryohsuke Yokosuka; Ryosuke Imai; Shosei Ro; Manabu Murakami; Kohei Okafuji; Atsushi Kitamura; Yutaka Tomishima; Torahiko Jinta; Naoki Nishimura; Tomohide Tamura; Osamu Takahashi (Canadian Respiratory Journal)
Background and Objectives. The concept of sarcopenia has been attracting attention in recent years, but its association with in-hospital mortality of patients with pneumonia is still unclear. Therefore, we investigated the relationship between pectoralis muscle mass on chest computed tomography (CT) and in-hospital mortality in patients with pneumonia. Methods. A retrospective cohort study was performed in patients aged 18 years or older with pneumonia who underwent chest CT within 24 hours of admission between April 2014 and March 2019. We measured the thickness, area, and volume of the pectoralis major and minor muscles at the level of the aortic arch. Factors associated with mortality were examined using logistic regression analysis. Results. A total of 483 patients (mean age 77 ± 14 years, 300 men (62%)) were included, and fifty-one patients (11%) died during admission. In univariate analysis, decreased thickness, area, and volume of the pectoralis major and minor muscles were associated with higher in-hospital mortality. Multivariate analysis with adjustment for age, gender, serum albumin, and A-DROP revealed that thinner pectoralis major and minor muscles were independent factors of poor prognosis (odds ratio: 0.878, 95% confidence interval (CI): 0.783–0.985, P=0.026 and odds ratio: 0.842, 95% CI: 0.733–0.968, P=0.016, respectively). Approximately 25% of the patients died when the pectoralis minor muscle thickness was 5 mm or less, and no patients died when it was 15 mm or more. Conclusion. The pectoralis muscle mass may be an independent prognostic factor in hospitalized patients with pneumonia.